Further evidence for eagle predation of, and feeding damage on, the Taung child. - Berger, L.R.; McGraw, W.S. (ASSAf, 2007)
We present new evidence supporting the hypothesis that a large raptor was responsible for the death of the c. 2.0-Myr-old Taung child, holotype of the early hominin species Australopithecus africanus. We compare the Taung child's skull with those of monkeys killed and eaten by modern crowned eagles, Stephanoaetus coronatus, in the Ivory Coast's Tai Forest. Close inspection of primate feeding remains from these large, powerful raptors reveals scratch marks in the orbital, frontal, temporal, parietal and occipital regions. Scratches similar in size and distribution are also present on the Taung child's skull. The new taphonomic evidence, combined with previously recognized similarities in breakage patterns and other assemblage characteristics, bolsters the case that a large bird of prey was responsible for the death of the juvenile hominin from Taung.
Keywords: feeding behavior; predation; primate; raptor; taphonomy